Isolation, characterisation and organisation of histone H1 genes in African trypanosomes - Grüter, Eric; Betschart, Bruno (My University, 2001)
A tandemly arranged gene family coding for histone H1 in African trypanosomes is described. Many variants, differing by some substitutions and/or deletions in their monotone and repetitive amino acid sequences, are found. The different variants can be sorted into three subtypes using their N-terminal region. PCR amplification experiments with primers specific to these three H1 subtypes suggest that the genes may be separated into two transcriptional units. Heterogeneity among species, subspecies and even strains was found. The transcripts are polyadenylated and the trans-splicing site is located very closely to the start codon. The intergenic regions are typical when compared to other polycistronic clusters described in trypanosomes. Amino acid sequence motifs may explain differences seen in chromatin compaction patterns between African and American trypanosomes.